The Influence of Fraud Triangle Theory on Academic Frauds High School Student Academics X - Oktari, Ripa; Taufik, Hilman; Susanti, Vinita (Faculty of Humanities, Universitas Jenderal Soedirman, 2024)
The phenomenon of academic cheating is very familiar to students where there are activities of cheating, making small notes, and asking friends during exams are acts of academic cheating. Academic cheating is a dishonest act by someone to gain personal gain unfairly. This study aims to show the triangle theory of fraud on academic cheating in high school X students. The independent variables in this study are pressure, opportunity, rationalization, and the dependent variable is academic cheating. This study used a questionnaire given to 54 respondents of grade 10 students registered at High School X. This study used multiple linear regression tests. The results showed that the pressure variable showed a positive number, meaning that the higher the pressure given to someone, the higher the possibility of academic cheating. The opportunity variable showed a negative number, meaning that the higher the opportunity obtained, the lower the possibility of academic cheating.